Judges' Consideration Of Polygamy Permits From The Perspective Of Positive Law And Islamic Law - Na'im, Arroyan; Fauzi, Mohammad Yasir; Zaki, Muhammad; Mohd Ridzwan, Farah Batrisya Binti (KALOSARA: Family Law Review, 2025)
Application for polygamy permit made at the Krui Religious Court level. One of the polygamy practices that occurs in society. This study aims to analyse the Panel of Judges of the Krui Religious Court in its legal considerations in deciding case Number 0251/Pdt/2016/PA.Kr concerning the granting of polygamy permits. This research method uses the judicial case study type, namely the application of normative Law to certain legal events that give rise to conflicts of interest. The results of this Judge's consideration are that the Applicant has met the facultative reasons according to the provisions of Article 4 paragraph (2) letter (a) in conjunction with Article 57 letter (a). And has met the cumulative requirements as stipulated in Article 5, paragraph (1) of Law Number 1 of 1974 concerning Marriage in conjunction with Article 55, paragraph (2) and Article 58 of the Compilation of Islamic Law. The purpose of this writing is to serve as study material for judges and legal experts, scholars and students. The results of the study show that positive Law and Islamic Law have differences in considering permission, but both have the same goal, namely, to achieve justice. Judges making their decisions are not only based on the Law but also on the provisions contained in Islamic Law, one of which is that the Panel of Judges relies on the word of Allah in QS Al-Nisa / 4: 3. The submission of polygamy on the grounds of avoiding adultery, then the Applicant considers polygamy as the right solution. The implication of this study is the importance of considering psychological and sociological aspects in dealing with sexual dysfunction in married couples. This study highlights the legal considerations and jurisprudence of judges in cases of polygamy and the integration of positive norms and Islamic law.Keywords: Judge's considerations, Positive Law, Islamic Law, Polygamy